A version of Krasnosel’skiĭ’s compression-expansion fixed point theorem in cones for discontinuous operators with applications - Figueroa, Rubén; López Pouso, Rodrigo; Rodríguez-López, Jorge (Topological Methods in Nonlinear Analysis, 2018)
We introduce a new fixed point theorem of Krasnosel’skiĭ type for discontinuous operators. As an application we use it to study the existence of positive solutions of a second-order differential problem with separated boundary conditions and discontinuous nonlinearities.